2021
DOI: 10.1590/1984-0462/2021/39/2020089
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Food Neophobia in Children: Systematic Review

Abstract: Objective: To identify the factors associated with food neophobia in children through a systematic review. Data sources: This research was based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The research was carried out in the PubMed, Science Direct, and Scientific Electronic Library Online databases, with the combination of health descriptors in English and Portuguese: (“Food Neophobia” OR “Feeding Behavior” OR “Food Preferences” OR “Food Selectivity”) AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…Another issue that often appeared to concern parents in the present study was food neophobia, which was severe in about 30% of the children. This finding is in accordance with most of the studies on food neophobia that report prevalence around 30% [ 59 ]. However, estimates of food neophobia prevalence vary widely in the international literature (from 12.8% to 100%) [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another issue that often appeared to concern parents in the present study was food neophobia, which was severe in about 30% of the children. This finding is in accordance with most of the studies on food neophobia that report prevalence around 30% [ 59 ]. However, estimates of food neophobia prevalence vary widely in the international literature (from 12.8% to 100%) [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with most of the studies on food neophobia that report prevalence around 30% [ 59 ]. However, estimates of food neophobia prevalence vary widely in the international literature (from 12.8% to 100%) [ 59 ]. This high variability is due to the diversity of tools used to measure food neophobia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observations associated with smell are consistent with the observations of Raudenbush et al [ 41 ], as they stated that individuals of high FN level have been found to rate odors as less pleasant and sniff odor samples less vigorously than those of low FN level. Such situation could be related to the psychological comfort, as in the recent systematic review of Torres et al [ 8 ], authors indicated that all actions associated with the emotional support and comfortable environment can stimulate curiosity about new shapes, colors and texture in children, which may be associated with their FN level. As a consequence, psychological comfort could reduce the level of neophobic behaviors and may contribute to increased positive experiences with food.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of Torres et al [ 8 ] presenting the issue of food neophobia (FN) in children, emphasized the role of this factor as one of the most significant determinants of nutritional behaviors. The FN may be studied while using the Food Neophobia Scale (FNS) by Pliner and Hobden [ 9 ], which is commonly applied, as it has been translated into various languages.…”
Section: Introductionmentioning
confidence: 99%